ANALISIS RASIO UNTUK MENILAI KINERJA KEUANGAN PADA PT MERCK INDONESIA TBK - Miftahurrohman Miftahurrohman; Reka Amelia (JURNAL LENTERA AKUNTANSI, 2021)
PT Merck Indonesia Tbk is a company engaged in the pharmaceutical sector. This study aims to determine the level of liquidity, solvency level, activity level, profitability level, and financial performance of PT Merck Indonesia Tbk for the last two years. Objects used in research This is the financial report of PT Merck Indonesia Tbk for 2017, and 2018 with the writing methodology used in the form of Library Research and Field Research . The technique used is ratio analysis, the types of financial ratios used are Current Ratio , Very Current Ratio ( Quick Ratio ) and Cash Ratio ( Cash Ratio ), Debt to Assets Ratio ( Debt to Assets Ratio ), Debt Ratio to Capital ( Debt to Equity Ratio ), Inventory Turnover Ratio ( Inventory Turnover Ratio ), Receivable Turnover Ratio ( Receivable Turnover Ratio ), Return On Investment ( ROI) Ratio, and Return On Equity Ratio ( ROE) ). The results showed that the level of liquidity, level of sovability, level of activity, level of profitability tend to be below the industry average ratio which indicates that the financial performance of PT Merck Indonesia Tbk is in poor condition.Keywords: Financial Reporting , Financial Ratio , Financial Performance